Skill-specific speed building aspects in different sport disciplines - Abzalov, R. A.; Abzalov, R. R.; Abzalov, N. I.; Valeev, A. M.; Abzalova, S. V. (Theory and Practice of Physical Culture, 2018)
The study analyzes the bodily adaptation specifics in different sport disciplines versus athletes` skill levels and speed qualities. The movement speed was tested by a laboratory computerized test system using standard tests. Subject to the study were skilled fencers, skiers and football players. It should be noted that fencing requires excellent speed qualities, and modern skiing sport requires high endurance, with both of the qualities being opposite. Football requires good speed-strength qualities and this was the reason for the footballers` tests for comparative analysis. We found that the higher are the sport skills the higher are the speed qualities, with the progress pace dependent on the specifics and intensity of the muscular loads i.e. the sport discipline; and identified the most sensitive periods in the speed building process. We believe that the speed qualities and speed endurance rating tests and studies of the relevant progress mechanisms should give the means to assess their contributions to the competitive accomplishments.